AL-QUR'AN DAN SENI DAKWAH: ANALISIS METODE WALISONGO DALAM MENYEBARKAN ISLAM DI JAWA - Wardah Robikhah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2026)
This study aims to analyze the relationship between the Qur'an and the art of da'wah in the methods employed by the Walisongo in spreading Islam throughout Java. Walisongo are widely recognized as Islamic missionaries who successfully integrated Qur'anic values with local culture and artistic traditions, enabling Islam to be accepted peacefully and effectively by Javanese society. This research employs a qualitative method with a library research approach by examining various relevant literature on Walisongo's da'wah, Javanese arts and culture, and Qur'anic principles that served as the foundation of Islamic propagation. The findings reveal that the utilization of artistic media such as wayang (shadow puppetry), gamelan music, traditional songs, and local cultural practices constituted a da'wah strategy deeply rooted in Qur'anic values, including wisdom (hikmah), good counsel (mau'izhah hasanah), and tolerance toward local traditions as long as they did not contradict Islamic teachings. The da'wah methods of Walisongo demonstrate that art can serve as an effective medium of communication for conveying Qur'anic messages to society. Therefore, the art-based da'wah approach exemplified by the Walisongo remains relevant for contemporary pluralistic and dynamic societies.